Reevaluating the Application of Contrarius Actus Principle in Land Case Resolution - Maloko, Fahruddin; Alting, Husen; Rumkel, Nam (Nurani Hukum, 2025)
This research addresses the urgent national issue of land disputes in Indonesia, where legal certainty is paramount. The National Land Agency (BPN) has the authority to cancel land certificates it issues, based on the contrarius actus principle, but its application is inconsistent across different types of land cases. This leads to legal ambiguity and a lack of effectiveness, particularly when third parties are involved. The novelty of this study lies in its focused analysis of this specific inconsistency, highlighting how the BPN's reluctance to use its authority in certain disputes undermines legal certainty. The research's will be contrributed on the of proposed regulatory overhaul to strengthen the BPN's authority to cancel certificates without causing unintended legal consequences, thereby ensuring more effective and fair resolution of land cases.